Fortune and glory [compact disc, unabridged] : tantalizing twenty-seven - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel., 2020)
When Stephanie's beloved Grandma Mazur's new husband died on their wedding night, the only thing he left her was a beat-up old easy chair... and the keys to a life-changing fortune. But as Stephanie and Grandma Mazur search for Jimmy Rosolli's treasure, they discover that they're not the only ones on the hunt. Two dangerous enemies from the past stand in their way-along with a new adversary who's even more formidable: Gabriela Rose, a dark-eyed beauty from Little Havana with a taste for designer clothes. She's also a soldier of fortune, a gourmet cook, an expert in firearms and mixed martial arts-and someone who's about to give Stephanie a real run for her money.